2014
DOI: 10.1179/1754762814y.0000000103
|View full text |Cite
|
Sign up to set email alerts
|

Family involvement in music impacts participation of children with cochlear implants in music education and music activities

Abstract: Objective Children with cochlear implants (CIs) participate in musical activities in school and daily lives. Considerable variability exists regarding the amount of music involvement and enjoyment. Using the Music Engagement Questionnaire-Preschool/Elementary (MEQ-P/E), we wanted to determine patterns of musical participation and the impact of familial factors on engagement. Methods Parents of 32 children with CIs (16 preschool, 16 elementary) completed a questionnaire regarding the musical involvement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 17 publications
(21 reference statements)
6
16
1
Order By: Relevance
“…Finally, in this study, parent participation in music significantly affected participation in music for children who are HH. This is consistent with research that shows children with CIs are more likely to consider music participation important if their family also places high value on music (Driscoll et al, 2015). Research on a different cohort of children who are HH who have less musically involved parents might therefore yield different outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Finally, in this study, parent participation in music significantly affected participation in music for children who are HH. This is consistent with research that shows children with CIs are more likely to consider music participation important if their family also places high value on music (Driscoll et al, 2015). Research on a different cohort of children who are HH who have less musically involved parents might therefore yield different outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…They therefore lack a reference to what music sounds like with NH and may develop compensatory music perceptual strategies. This has been argued to be the case with children who use CIs, who show higher rates of music enjoyment than adults who use CIs (Driscoll et al, 2015). Another possibility is that parents of children who are HH may be conscious of the importance of auditory input and are therefore vigilant about encouraging their child to participate in music.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect has been previously addressed in studies looking to describe the musical home environment of infants and young children [ 28 ], [ 30 – 31 ], [ 43 ], [ 64 65 ] or exploring music-related parental attitudes in relation to music educational outcomes [ 41 ], [ 66 69 ]. These studies have shown that parents’ whose children participate in music classes usually have positive beliefs towards the general educational benefits and significance of music practice [ 66 ], [ 68 ], and that parental attitudes can be positively associated with children’s musical attainment and motivation [ 41 ], [ 67 ], [ 69 ]. Furthermore, the majority of parents of preschoolers who expressed positive beliefs about the benefits of music education also reported high frequency of singing and listening to music with their children [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is a lack of control intervention, which is important to examine effects of procedural learning (Jiam et al, 2019). Fourth, attentive listening appears to be feasible for adult patients, but it is a challenge for pediatric patients, who may need familial involvement and more interesting training methods to boost patients' engagement (Driscoll et al, 2015). Finally, the FCDT test only involved pure tones rather than complex stimuli.…”
Section: Limitations and Future Studiesmentioning
confidence: 99%